Understanding Nursi’s contribution towards a worldview-bound education for Muslim world - Paramboor, Jafar; Ibrahim, Mohd Burhan (2016)
Since a worldview is developed by a natural process from an everyday life continuity of a society (Alparsalan, 1996), the social situation of a community has a key role in molding its own worldview. Starting from a context of individual setting, the formation and development of a worldview is influenced by the social setting which is to be interpreted using different methods of understanding. The main focus of this paper would be on giving an outline of how Said Nursi contributed to a worldview-bounded education for Muslim world. While analyzing the philosophy and thought of Nursi with special reference to his writings by which the identity of an eminent intellectual figure was and is being established, the paper would be looking into the relation of his educational ideologies with the established worldview which is Islamic in nature. The notion of worldview both from secular and Islamic environment would be analyzed in order for the „worldview-bound education‟ to be clear. The understanding of Nursi‟s contribution is made by philosophically analyzing and interpreting four cases taken from his own writings. The observations obtained from a systematic analysis of these cases would be underpinning the fact that the educational institutions of Islamic world should give better concern on reading Said Nursi‟s intellectual contributions to Muslim education system.